2005
DOI: 10.2307/3473310
|View full text |Cite
|
Sign up to set email alerts
|

Sex Ratios under Asymmetrical Local Mate Competition: Theory and a Test with Parasitoid Wasps

Abstract: Sex ratio theory allows unparalleled opportunities for testing how well animal behavior can be predicted by evolutionary theory. For example, Hamilton's theory of local mate competition (LMC) is well understood and can explain variation in sex allocation across numerous species. This allows more specific predictions to be developed and tested. Here we extend LMC theory to a situation that will be common in a range of species: asymmetrical LMC. Asymmetrical LMC occurs when females lay eggs on a patch asynchrono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
82
1
3

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(89 citation statements)
references
References 11 publications
3
82
1
3
Order By: Relevance
“…However, females produce less-biased, or even male-biased, sex ratios, depending on the number of other females (foundresses) ovipositing together on a host and the relative clutch sizes produced by those females (Hamilton 1967;Werren 1980;). While we have a detailed understanding of the information used by female Nasonia during sex allocation (e.g., Werren 1980Werren , 1983King et al 1995;Shuker and West 2004;Shuker et al 2005Shuker et al , 2006aBurton-Chellew et al 2008), we have only a rudimentary understanding of the genetic basis of sex allocation (Pannebakker et al 2008(Pannebakker et al , 2011(Pannebakker et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…However, females produce less-biased, or even male-biased, sex ratios, depending on the number of other females (foundresses) ovipositing together on a host and the relative clutch sizes produced by those females (Hamilton 1967;Werren 1980;). While we have a detailed understanding of the information used by female Nasonia during sex allocation (e.g., Werren 1980Werren , 1983King et al 1995;Shuker and West 2004;Shuker et al 2005Shuker et al , 2006aBurton-Chellew et al 2008), we have only a rudimentary understanding of the genetic basis of sex allocation (Pannebakker et al 2008(Pannebakker et al , 2011(Pannebakker et al , 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Females lay clutches of 20-40 eggs and limit oviposition in previously parasitised hosts (superparasitism) if possible (e.g. Werren 1980Werren , 1984Charnov and Skinner 1984;Shuker et al 2005). Since N. vitripennis is haplodiploid, females are assumed to be able to facultatively alter the sex ratio by choosing whether or not to fertilise an egg (producing diploid females or haploid males, respectively).…”
Section: Study Organismmentioning
confidence: 99%
“…Immature survival may be sex-specifi c if male and female larvae have different nutritional requirements or if one sex is a better competitor than the other (Ode et al, 1996;van Baaren et al, 1999;Sykes et al, 2007;. In addition, a female may alter her offspring sex-allocation strategy if she encounters parasitized hosts (Werren, 1984;Shuker et al, 2005;Diaz-Fleischer et al, 2015) or other females searching the same patch (Wylie, 1979;Visser, 1995;Ito & Yamada, 2016). For example, van Baaren et al (1999) reported that superparasitizing females of Anaphes victus Huber (Hymenoptera: Mymaridae), a solitary egg parasitoid, produced a more male-biased sex ratio than females attacking unparasitized eggs; however, the sex ratio at eclosion was unchanged because male larvae suffered proportionately higher mortality than their female counterparts.…”
Section: Introductionmentioning
confidence: 99%